Kelengkapan Penyajian Laporan Keuangan Terhadap Fraud Detection Dengan Di Moderasi Good Corporate Governance Era Covid-19 - Oza Restianita; Khavid Normasyhuri; Muhamad Kurniawan (Jurnal Akuntansi dan Pajak, 2023)
The pandemic due to Covid-19 has had an impact on the sustainability of companies including banking institutions. Many banking companies experienced financial difficulties. The financial and cash flows owned by the company are very vulnerable to various problems caused by financial transaction activities that drop significantly and drop periodically. But on the other hand, the disruption of deteriorating economic conditions and the diversion of the focus of all parties to the Covid-19 pandemic crisis and weak oversight have created opportunities for fraud. This research was conducted with the aim of looking at the effect of completeness in the presentation of financial statements on fraud detection in Indonesian sharia commercial banks in the Covid-19 era through Good Corporate Governance (GCG) as a moderating variable. This research includes quantitative research with a moerator approach. This study uses secondary data derived from the financial reports of Indonesian Sharia Commercial Banks during the Covid-19 era in the 2020-2022 period. The sampling technique used is purposive sampling. The statistical software used is SPSS Version 25. The results showed that the completeness of financial reports has a positive and significant effect on fraud detection. The audit committee strengthens the positive influence of the completeness of financial statement presentation on fraud detection.